Limit states for post-earthquake assessment and recovery analysis of ductile concrete components. Issue 2 (May 2023) - Opabola, Eyitayo A; Abdullah, Saman A; Elwood, Kenneth J; Wallace, John
Post-earthquake assessment procedures require component deformation limits to identify locations for visual inspection and locations needing structural repair. This study proposes a framework for defining component deformation limits for detailed visual inspection and repair for earthquake-damaged concrete buildings. First, observations from cyclic tests of ductile concrete components (beams, columns, and walls) suggested that the residual capacity (in terms of strength and deformation capacity) of such components is likely uncompromised if the deformation at the initiation of lateral strength loss (LSL) is not exceeded in prior loading histories. The results also revealed that the deformation at the initiation of LSL typically corresponds to the onset of longitudinal bar buckling in ductile components. Furthermore, using experimental data, multipliers are developed as fractions of ASCE/SEI 41 modeling parameters at lateral failure (i.e. a or d ) to predict deformation at initiation of LSL. Subsequently, a probabilistic approach is proposed for defining the component deformation limits, considering uncertainty in both capacity and demand. Component deformation limits for detailed visual inspection are defined such that there is a low probability (adopted as <10%) of exceeding the deformation at the initiation of LSL. The component deformation limit for repair is defined as the median deformation at the initiation of LSL (i.e. 50% probability of exceedance).